Effect of the Lacuna Distribution on Stress and Strain in Single Osteon - Ismail, A.A; Daud, R.; Omar, M.I.; Junoh, A.K.; Zain, N.A.M. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
In order to understand bone behaviour and bone failure behaviour, this study aimed to investigate stress distribution and strain developed in a single osteon with a different number of lacunae when a compressive load was given. Finite element (FE) analysis of single osteon was developed, one osteon with no lacuna (Model A) and three osteon models with a different number of lacunae (10 lacunae = Model B, 8 lacunae = Model C, 6 lacunae = Model D). The single osteon is developed as a semi-circle due to symmetric structure, with the presence of Haversian canal at the centre in each model. Stress distribution in Model B, Model C and Model D were shown to yield the highest stress at the lacuna near the given load and Model A was shown to yield maximum stress near the Haversian canal. The maximum strain of Model B, Model C and Model D were measured at the ellipse lacuna near the load while the maximum strain of Model A was shown at lamella near Haversian canal. These investigated results for the stress distribution and strain in the osteon can be used in the study to determine the yield region in osteon in bone fracture study.